Consumers’ Knowledge, Understanding and Use of Food Label Information, and How it Affects Purchasing Decision in Ho, Ghana - Affram , Priscilla Cecilia; Darkwa, Sarah (Asian Journal of Empirical Research, 2015)
The main objective of the study was to assess consumers’ knowledge, understanding and use of food label information. Data was collected from the capital city of Ho Municipal district in the Volta Region of Ghana using a Survey questionnaire and observation. Participants were adults, aged 18-65 years (n=600; 53%, 47%) randomly selected to assure increased response rate. Observation, reading, knowledge, understanding and use of food label- information were the main outcome measures used. Chi–square and Kruskal test were used to assess differences in participants’ characteristics and use of food labeling in food purchase. Findings showed high awareness (P< 0.05) and frequency in food label reading among participants but this did not necessarily influence their purchase of food. Insufficient knowledge, time constraints and small font sizes were reported by participants as the main factors that prevented them from reading and using food label. Although sex (P<0.89) did not influence participants’ reasons for reading labels, age did at P< 0.01. Younger consumers read labels to compare products; older ones did so out of curiosity and for special dietary needs. Knowledge, understanding and use of food label information did not significantly differ with gender but did with age. Understanding food labels through education is needed to promote use among both young and old consumers.